The effect of goal setting in asthma self-management education: A systematic review - Yaoji Liao; Guozhen Gao; Yaqing Peng (Elsevier, 2019)
Background: Asthma self-management education combining with behavior therapy is considered to be more effective. Goal setting is a common behavior change technique used to help patients self-manage their symptoms. However, empirical evidence around its effectiveness on asthma management lacks clarity. Aims: To systematically integrate and appraise the evidence for effectiveness of goal setting interventions on asthma outcomes. Methods: Databases included CENTRAL, PubMed, EMBASE, CINAHL and Proquest Psychology Database were systematically searched for relevant intervention studies employing goal setting technique as a method in asthma education program for self-management. Characteristic of studies and outcomes in clinical, psychosocial and healthcare utilization outcome were extracted. Results: From a total of 2641 citations, 45 full-text articles were assessed for eligibility and 9 studies met the inclusion criteria. Eight studies were randomized controlled trial and one was before-after study. None studies have a high methodological quality. Goal-setting based intervention appeared to improve symptom control, quality of life and self-efficacy in adult patients with asthma. Conclusion: This systematic review highlighted the potential of a goal setting technique in the asthma self-management education. However, due to the limitations of the quality and quantity of the included literature, more rigorous studies are needed. In the future, better effective study protocol combining with goal setting approach and other behavior technique is needed to further investigate. Keywords: Asthma, Goal setting, Patient education, Self-management